Factors Affecting the Improvement of Cassava Cracker Business - Sri Hariyani; Riski Nur Istiqomah Dinnullah; Nur Jahan Ahmad (Journal of Nonformal Education, 2024)
In the dynamic landscape of the cassava cracker business, staying informed about the ever-evolving factors influencing its improvement is crucial for sustainable success. The purpose of this study was to determine the effect of the implementation of KKN-T MBKM activities carried out by students of the Mathematics Education Study Program on increasing the business of cassava crackers SMEs. KKN-T is a nonformal education but provides an important role not only for students but also for the community. The method used in this study is binary logistic regression analysis. The data used is primary data by distributing questionnaires to 20 respondents who are partners in KKN-T activities. The technique used in this data collection is to use a purposive sample technique. The results of the study indicate that the influencing factors are: quality of information analysis according to partner needs; student contributions to partners; the contribution between the contribution and the needs of partners; student contributions provide benefits for partners; and student contributions can motivate an increase in value/quality of life. Meanwhile, based on the simulation of utility variables, it can be seen that the variables that have a significant effect on increasing SME business will provide an opportunity for an increase in the business of 99.68%. This research contributes knowledge related to the implementation of binary logistic regression in analyzing the influence of implementing KKN-T MBKM activities carried out by Mathematics Education Study Program students on increasing the cassava cracker UKM business.